Spin–orbit coupling in the presence of strong atomic correlations. (23rd January 2020) - Usui, Ayaka; Fogarty, Thomás; Campbell, Steve; Gardiner, Simon A; Busch, Thomas
Abstract: We explore the influence of contact interactions on a synthetically spin–orbit coupled system of two ultracold trapped atoms. Even though the system we consider is bosonic, we show that a regime exists in which the competition between the contact and spin–orbit interactions results in the emergence of a ground state that contains a significant contribution from the anti-symmetric spin state. This ground state is unique to few-particle systems and does not exist in the mean-field regime. The transition to this state is signalled by an inversion in the average momentum from being dominated by centre-of-mass momentum to relative momentum and also affects the global entanglement shared between the real- and pseudo-spin spaces. Indeed, competition between the interactions can also result in avoided crossings in the ground state which further enhances these correlations. However, we find that correlations shared between the pseudo-spin states are strongly depressed due to the spin–orbit coupling and therefore the system does not contain spin–spin entanglement.